First Report of Sex Chromosomes in Plated Lizards (Squamata: Gerrhosauridae) - Kostmann, Alexander; Kratochvíl, Lukáš; Rovatsos, Michail (Sexual development, 2020)
Squamate reptiles show high diversity in sex determination ranging from environmental sex determination to genotypic sex determination with varying degrees of differentiation of sex chromosomes. Unfortunately, we lack even basic information on sex determination mode in several lineages of squamates, which prevents full understanding of their diversity and evolution of sex determination. One of the reptilian lineages with missing information on sex determination is the family Gerrhosauridae, commonly known as the plated lizards. Several species of gerrhosaurids have been studied in the past by conventional cytogenetic methods, but sex-specific differences were not identified. In this study, we applied both conventional and molecular cytogenetic methods to metaphases from both sexes of the Peters' keeled plated lizard (Tracheloptychus petersi). We identified accumulations of rDNA loci in a pair of microchromosomes in metaphases from males, but only in a single microchromosome in females. The restriction of the observed heterozygosity to females suggests a putative ZZ/ZW system of sex chromosomes, which represents the first report of sex chromosomes in a gerrhosaurid lizard. The lack of sex-specific signals in all other cytogenetic methods implies that the sex chromosomes of T. petersi are poorly differentiated in sequence content.
Keywords: Sex chromosomes; FISH; CGH; rDNA; Telomeres